Beyond the Battlefield: Tracing War, Psychological Trauma, And Liminality in Shimmer Chinodya’s Harvest of Thorns (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
This article challenges the nationalistic war accounts of the Zimbabwe’s liberation struggle that focused primarily on the political conquest where individuals’ contribution and their psychological experiences were not given the recognition they deserved.  Hence, a critical survey of Shimmer Chinodya’s Harvest of Thorns (1989) through the intersecting lenses of war, psychological trauma, and identity reconstruction investigates the novel’s depiction of Zimbabwe’s liberation fight and its aftermath. Going beyond the patriotic war accounts that centered on political victory, the novel interrogates the lives of ex-combatants, using the character of Benjamin, whose post-war survival is characterized by psychological breakdown and emotional disruption. This paper, however, contends that Chinodya criticizes the patriotic exaltation of war revealing the unseen wounds endured by individuals, particularly those whose identities have been broken by ideological revolution and battlefield brutalities. Relying on trauma theory of liminality, therefore, the study analyzes how Harvest of Thorns (1989) recounts the silent, ongoing combats that endure long after the hostility ends- those fought within the mind and soul of the traumatized victim. Finally, the article reveals that real liberation entails not only political sovereignty but also emotional healing of the ex-combatants and a reimagining of selfhood in post-conflict societies.Keywords: , , , ,
Keywords: Combatants; liberation war; liminality; trauma; identity